Morphologically controllable synthesis of core–shell structured Au@Cu2O with enhanced photocatalytic activity1. Issue 88 (25th September 2015) - Yuan, Guotao; Lu, Mengna; Fei, Jiuhui; Guo, Jun; Wang, Zuoshan
<x xml:space="preserve">Abstract</x> Core–shell structured Au@Cu2O nanocomposites with different morphologies were prepared by a facile solution route.